2021
DOI: 10.1186/s13756-021-01010-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the Global Point Prevalence Survey of Antimicrobial Consumption and Resistance (Global-PPS) on hospital antimicrobial stewardship programmes: results of a worldwide survey

Abstract: Background The Global Point Prevalence Survey of Antimicrobial Consumption and Resistance (Global-PPS) provides a methodology to support hospitals worldwide in collecting antimicrobial use data. We aim to evaluate the impact of the Global-PPS on local antimicrobial stewardship (AMS) programmes and assess health care professionals’ educational needs and barriers for implementing AMS. Methods A cross-sectional survey was disseminated within the Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“… 3 A recent study found that local, evidence-based AMS guidelines were used in 96% of North American hospitals, compared with 77% in Latin America, 72% in Europe and 76% in Asia. 8 AMS facilitators’ efforts were in-person training for a range of HCPs, locally relevant evidence-based guidelines and the establishment of a multidisciplinary team who monitor and manage AMS. 8 Given education is a known facilitator to implementation, it is essential to gain a better understanding of the educational needs and current practice gaps that might hinder the implementation of strategies aimed to enhance adherence to AMS principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 A recent study found that local, evidence-based AMS guidelines were used in 96% of North American hospitals, compared with 77% in Latin America, 72% in Europe and 76% in Asia. 8 AMS facilitators’ efforts were in-person training for a range of HCPs, locally relevant evidence-based guidelines and the establishment of a multidisciplinary team who monitor and manage AMS. 8 Given education is a known facilitator to implementation, it is essential to gain a better understanding of the educational needs and current practice gaps that might hinder the implementation of strategies aimed to enhance adherence to AMS principles.…”
Section: Introductionmentioning
confidence: 99%
“… 8 AMS facilitators’ efforts were in-person training for a range of HCPs, locally relevant evidence-based guidelines and the establishment of a multidisciplinary team who monitor and manage AMS. 8 Given education is a known facilitator to implementation, it is essential to gain a better understanding of the educational needs and current practice gaps that might hinder the implementation of strategies aimed to enhance adherence to AMS principles. 9 To identify the educational needs of HCPs in AMS, this study assessed the current knowledge, skills and beliefs of HCPs, in addition to systemic barriers that obstruct adherence to AMS principles, which is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The study was carried out in the second half of 2021 as a part of the international Global-PPS Project [ 13 ] using the conventional point prevalence study methodology [ 16 ]. PPS is a universal tool that allows information to be obtained on the use of AMD in hospitalized patients to reveal the main problems and develop targeted measures as a part of local AMS programs and to monitor the effectiveness of their implementation [ 12 , 17 ]. The results of the study will provide a basis for the development of appropriate stewardship activities, tailored according to local practices for each multi-field hospital in the project in the COVID-19 pandemic period and thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Still, information on antimicrobial consumption and prescribing in inpatients with COVID-19 in Russian hospitals remains sparse and understudied. Point prevalence studies (PPS) have established themselves as a convenient, low-cost, and at the same time standardized and validated tool for monitoring the prescribing of drugs in inpatients to aid antimicrobial stewardship (AMS) activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…44 There are three survey periods for data collection within the calendar year and at the end of 2018, and Global-PPS has been used in over 700 hospitals in more than 70 countries worldwide. 43 The Global-PPS auditing tool collects detailed data on patient demographics, antimicrobial regimen, indication by diagnostic codes, and intention (prophylaxis, empirical, or targeted therapy). Similar to the NHSN AU and AR module, microorganisms by resistance type is categorized and reported.…”
Section: How Do Current Antimicrobial Stewardship Auditing Tools Comp...mentioning
confidence: 99%